Analysis of Complete Blood Count (Cbc) and Erythrocyte Sedimentation Rate (Esr) Results in Multidrug Resistant Tuberculosis (Mdr-Tb) Patients - Christina Destri Wiwis Wijayanti; Dheasy Herawati; Annisa Annisa Juniati (Green Publisher Indonesia, 2024)
Tuberculosis (TB) is a contagious infectious disease caused by the bacterium M. tuberculosis. The emergence of drug-resistant strains of Mycobacterium tuberculosis causing MDR-TB is one of the public health problems to date. Globally, it is estimated that there will be 450,000 incident cases of MDR-TB in 2021, up 3.1% from 437,000. The danger of side effects that can arise in tuberculosis patients during MDR-TB treatment is that one of them is a decrease in the number of erythrocytes, the number of leukocytes and platelets. The purpose of this study was to analyze the results of Complete Blood Count (CBC) and ESR in Multidrug Resitant Tuberculosis (MDR-TB) patients at the University Hospital of Muhammadiyah Malang. This study is an observational descriptive study with data sourced from primary data collection. The samples of this study were positive MDR-TB patients from TB-RO clinic of RSU Universitas Muhammadiyah Malang as many as 25 samples, examined in October-November 2023, male and female. The data were analyzed descriptively using tables and graphs. The results of the study averaged more than 50% in the components of hemoglobin, hematocrit, and erythrocyte count decreased. In the platelet count examination component, 32% on average decreased. The average leukocyte count component of 92% tends to be normal. The examination of ESR is not specific for MDR-TB patients, namely the female gender has increased (elongated) while the male gender tends to be normal.